Badudus Tradition in South Kalimantan with Hope from a Psychological Perspective: Tradisi Badudus Di Kalimantan Selatan dengan Hope dalam Sudut Pandang Psikologi - Helvyra Priantini; Listyo Yuwanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Indonesia possesses a diverse array of cultures and traditions that are distinctive, and one intriguing tradition in Indonesia is the Badudus tradition in Kalimantan. This tradition involves the purification of the soul and body before marriage. The research methodology employed for this study involves a literature review of 10 journals spanning from 2013 to 2023. The Kalimantan community believes that the Badudus tradition is essential and should not be overlooked, attributing a sense of hope to this practice. People anticipate positive outcomes from engaging in this tradition